2022
DOI: 10.1111/jonm.13646
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence and robot nurses: From nurse managers' perspective: A descriptive cross‐sectional study

Abstract: Aim This research was planned to identify nurse managers' opinions on artificial intelligence and robot nurses. Background As the concepts of artificial intelligence and robot nurses are becoming widespread in Turkey, nurse managers are expected to guide and cooperate with nurses in the future in regard to these technologies. Methods The sample of the study consisted of 326 manager nurses, who were reached via the online questionnaire during the period of September to November 2021. A Nurse Managers Informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 34 publications
1
8
0
1
Order By: Relevance
“…In this study, more than half of the participating operating room nurses stated that robots would reduce their workload. Consistent with the results of this study, in Ergin et al’s [ 22 ] study involving nurse managers more than half of them thought that robotic nurses would benefit the nursing profession. In Alcan et al’s [ 18 ] study conducted to determine the views of nurses on robotic surgery, 68.9% of the 286 nurses stated that they would prefer robotic surgery if they were to undergo surgery in the future.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, more than half of the participating operating room nurses stated that robots would reduce their workload. Consistent with the results of this study, in Ergin et al’s [ 22 ] study involving nurse managers more than half of them thought that robotic nurses would benefit the nursing profession. In Alcan et al’s [ 18 ] study conducted to determine the views of nurses on robotic surgery, 68.9% of the 286 nurses stated that they would prefer robotic surgery if they were to undergo surgery in the future.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the majority of the participating nurses ( n = 25) stated that they did not think that robots would replace nurses. In the literature, there is a consensus among authors that artificial intelligence robots will not directly replace nurses in the near future [ 22 , 28 32 ]. However, contrary to this study results, in their study, Abdullah and Fakieh [ 23 ] investigated the perceptions and attitudes of healthcare professionals toward the application of artificial intelligence technologies in healthcare institutions in Saudi Arabia, and they reported that most of the participants were worried that artificial intelligence would replace them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 In addition, the training of personnel such as surgical nurses as regards AI and the role of this including robotic nurses and how to program these-if indicated-remains an area of concern. 48 At present, more robust clinical data across many spheres of health, including later life, that can yield large reliable data sets that cover the most universal features of rehabilitation need are clearly required to successfully advance the health opportunities for aging populations at high risk for so many diverse chronic health situations and experiences in a meaningful and safe manner. Their application must also prove to minimize costs, have no adverse climate change impact, be practical, and be mindful of past and pervasive health disparities, equity issues, and complex cultural and genetic influences.…”
Section: Discussionmentioning
confidence: 99%
“…Looking ahead, nurses will continue to be an integral and irreplaceable component of any health care model, despite possible shifts in the professional landscape. Research has been conducted to address the question, “Can AI replace nurses?” The consensus is that robots are not seen as substitutes for nurses 11 ; instead, AI-driven health technologies are recognised for their potential to enhance nursing practice. This is exactly what the profession and discipline of nursing needs to enable our nurses to envision a future and foster socially sustainable and healthy economies.…”
mentioning
confidence: 99%